Impact of retirement transition on health, well-being and health behaviours: critical insights from an overview of reviews - Vigezzi, Giacomo Pietro; Barbati, Chiara; Maggioni, Elena; Stenholm, Sari; Odone, Anna; Italian Working Group on Retirement and Health; Amerio, A.; Ardito, C.; Bertuccio, P.; Costa, G.; d’Errico, A.; Gentile, L.; et al. (Elsevier BV, 2025)
Retirement is a pivotal life course transition wich may have profound implications for health, well-being and health behaviours. Despite extensive research and theoretical debate, the impact of retirement on health remains inconclusive, with studies reporting positive, negative, or no effects. This overview of reviews synthesises evidence from 15 systematic reviews (4 meta-analyses) assessing the relationship between retirement and physical and mental health outcomes (including mortality, mental health, cognitive decline and cardiovascular diseases) and health behaviours (including physical activity, diet, smoking and alcohol consumption). The review adheres to PRIOR guidelines and assesses the quality of the literature and existing methodological challenges. Findings indicate that retirement's impact varies widely depending on socioeconomic status (SES), job characteristics, and individual lifestyle factors. Retirees with higher SES generally experience improved mental health and increased physical activity, whereas those with lower SES are more prone to declines in physical and mental health, increased sedentary behaviour, and adverse cardiovascular outcomes. Evidence on cognitive decline and mortality remains mixed. This review highlights critical methodological issues in the available literature, including inconsistent definitions of retirement, reliance on self-reported health data, and biases like reverse causality and healthy worker effect. Future research should prioritise life course longitudinal designs and cross-country comparisons informed by stronger theoretical grounding to untangle the complex relationship between retirement and health. Policy efforts should target vulnerable groups, particularly those from lower SES, by promoting physical activity, mental well-being, and social engagement during and after the transition to retirement. Tailored interventions across retirement transition could mitigate health disparities and improve overall well-being in later life.